Determinants of mobile wallet adoption and recommendation: An empirical assessment in merchants - Acosta Enriquez, Benicio Gonzalo; Vilcapoma Perez, César Robin; Arbulú Ballesteros, Marco Agustín; Montes Ninaquispe, Jose Carlos; Pantaleón Santa María, Alberto Luis; Guzmán Valle, María De Los Ángeles; Mogollón García, Francisco Segundo (LACCEI, 2023)
The study made it possible to evaluate the determinants of mobile wallet adoption and recommendation among Peruvian merchants. Methodologically, the study was based on a quantitative approach, with a non-experimental, descriptive design, using a survey and a questionnaire as techniques. The population consisted of merchants, users of the electronic wallet, Trujillo, 2023. The results concluded that: (1) The study conducted an empirical evaluation of the factors that influence the adoption and recommendation of digital wallet services of the UTUAT2 model in the Peruvian context, empirically corroborating the significant prevalence of seven factors. (2) Ease of use, perceived usefulness, attitude and perceived satisfaction, presented high levels of perception by merchant users of mobile wallet services, which would explain the massive increase of users during the Covid-19 pandemic and in the post-pandemic stage. (3) Perceived risk of inappropriate or malicious use of personal information and insecurity also showed high levels of perception by merchant users of mobile wallet services. (4) Intention to use and recommendation of mobile wallet services also showed high levels of perception by merchant users, which explains the massive popularity of these services.